The Effect of Benfotiamine on Mu-opioid Receptor Mediated Antinociception in Experimental Diabetes - Nacitarhan, C.; Minareci, E.; Sadan, G. (Experimental and Clinical Endocrinology & Diabetes, 2014)
Diabetic neuropathy is a prevalent, disabling disorder. Currently, the only treatments available to patients with diabetic neuropathy are glucose control and pain management. B vitamin present neuroprotective effects, which are suggested to be related to their analgesic action in various models of neuropathic pain. According to our literature knowledge there is no report about antinociceptive effects of thiamine as benfotiamine and opioids together in diabetic mice. The purpose of this study was to determine the effects of benfotiamine on the antinociception produced by mu-opioid receptor agonist fentanyl in diabetic mice. The effects of benfotiamine on antinociception produced by fentanyl in diabetic mice were studied in 4 groups. Antinociceptive effect was determined with tail flick, hot plate and formalin test. Our results showed that, mu-opioid agonist fentanyl in benfotiamine applied diabetic group caused more potent antinociceptive effect than in diabetic group without benfotiamine treatment. In brief benfotiamine supplement in diet did not bring out antinociceptive effect itself, but during development of STZ diabetes, benfotiamine replacement increased the antinociceptive effect of fentanyl in mice tail-flick test. This effect is probably due to the replacement of benfotiamine efficiency occuring in diabetes mellitus. Finally, we suppose that oral benfotiamine replacement therapy may be useful to ameliorate analgesic effect of mu-opioid agonists on neuropathic pain in diabetic case.
Keywords: diabetic neuropathy; benfotiamine; nociception; opioid